(untitled) (Bangladesh Journal of Pharmacology, 2018)
An endophytic fungus Chaetomium cupreum was isolated from the ornamental plant Mussaenda luteola. A known metabolite named resorcinol type of lipid (compound 1) was isolated using column chromatography and structurally elucidated by spectroscopic studies includes UV-Vis, FT-IR, NMR, MS analysis and comparing with the existing data. The compound 1 was evaluated for antimycobacterial potential by microtitre plate alamar blue assay against Mycobacterium tuberculosis H37Rv (ATCC27294). It also estimated for DPPH free radical scavenging and antibacterial (agar well diffusion method) potentials. Compound 1 revealed to have significant inhibition of Mycobacterium with MIC of 6.3 µg/mL which is similar to the standard streptomycin drug. It also exhibited good DPPH free radical scavenging potential of 84.5 ± 0.4% and maximum inhibition of both E. coli (ATCC 25922) as well as S. aureus (ATCC 25923). Thus, endophytic fungus C. cupreum from Mussaenda luteola could be a potential source of novel lead antimicrobial agents for drug discovery. Video Clip of Methodology: 9 min 43 sec: Click to watch